Enhancing Learning Interest in the Collaborative Learning Practitioner Lecture: Training on Determining the Viscosity of Palm Kernel Oil (PKO) - Aminati, Salmah; Purwiandono, Gani (Universitas Islam Indonesia, 2024)
This study aims to determine the effects in physical chemistry class with the workshop sessions on measuring PKO viscosity by CV. Bina Agro Mandiri. The effects are evaluated through the enhancing of student's learning interest in the Physical Chemistry II class in Chemistry Program of the Islamic University of Indonesia, which presents a good avenue for this investigation. The study was conducted by classroom, practical and online action. The data were analyzed using a pie chart. Findings showed that the implementation of the practical was able to increase the student's learning interests. Through case analysis tasks, students participate significantly in the teaching-learning process.